A study on promotional mix of Sarawak Cultural Village / Hawa Haji Nahar - Haji Nahar, Hawa (1999)
This is a study on the promotional aspect of Sarawak Cultural Village (SCV) in promoting Sarawak Cultural Village locally and abroad. It is carried out to fulfill the requirements of BACHELOR IN BUSINESS ADMINISTRATION (HONS) MARKETING. The paper tries to provide an indepth analysis on the effectiveness of promotion carried out all this while based on feedback given by the visitors of Sarawak Cultural Village. This could be as the guide lines for Sarawak Cultural Village to reexamine and improve its promotional strategy. Visitors in this context refers to the local people known as Sarawakian, West Malaysian and Sabah as Non Sarawakian and tourists known as overseas guest who visited and intended to visit SCV. Prior to writing this paper, a survey was conducted in March 1999 where personal interviews with the ministry, agencies and individual concerned were carried out and questionnaires were distributed the the local people and tourists. Desk research were also carried out through SCV reports, magazines, journals, newspaper cuttings and selected text books. The findings ofthe survey clearly shows that the visitors especially the tourist knew cultural village through guide books. Also the study revealed that promotion is very important for Sarawak Cultural Village. However, the general comment is that not only the SCV should be promoted aggressively, but also the destination itself, particularly Sarawak and Malaysia as a whole. Generally, the tourist only knew Malaysia is somewhere in Asia. This will discourage them from making the decision to visit Sarawak and to SCV. As such, aggressive promotion must be done not only by SCV but also by the Ministry of Tourism Malaysia and the Information Center for Malaysia throughout the world.